(untitled) (CAHIERS MAGELLANES-NS, 2024)
The principle of mixing and diversity in land uses is one of the most important indicators addressed by most contemporary planning studies, trends and approaches in order to achieve urban sustainability, as well as It is considered an effective tool. To compare cities and urban areas in terms of balanced and diverse distribution of land uses, as it also supports sustainable transportation patterns (walking and cycling) and provides easy access to events and activities due to the proximity feature. Which supports the quality and type of integrated urban infrastructure features, as there is a close relationship between increased walking and health and well-being indicators. [1] It is expected that if the phenomenon of rapid changes continues at the level of the strip streets towards commercial and mixed use within the residential alleys, which gives them the advantage of functional diversity, mixing land uses and increasing density locally, this is one of the principles of urban sustainability, but it is an unplanned and random act, which may have negative effects on the population more than its positives. At the same time, the intensive increase in commercial activity on the main streets and the diversity of activities in a mixed manner between wholesale and retail trade, restaurants, fitness centers, banks and shopping centers has led to an increase in the economic value and prices of land and made it a desirable area for housing and work as well, due to the availability of social and marketing services and ease of access to it. [2]